FACTORS AFFECTING THE LOCATION OF ECONOMIC ACTIVITIES: A MULTI-DISCIPLINARY REVIEW AND CONCEPTUAL FRAMEWORK - Bam, Wouter Gideon; De Bruyne, Karolien; Schutte, Corne (The South African Journal of Industrial Engineering, 2020)
A holistic framework that enables a systematic evaluation of the factors affecting the location of economic activities has thus far been lacking. Using a structured review, this research summarises the key developments that address this issue. Based on this review, a conceptual framework is proposed. The framework is location-centric — i.e., it evaluates the performance of a location in supporting a specific activity aimed at a particular market. It aims to assist both firms and policymakers to evaluate the key location determinants that drive the location of activities.